Hidrogeomorfologi mata air stratovolkano di area Celah Selo Jawa Tengah - Muhammad Asrori Indra Wardoyo; Nurul Khotimah (Geo Media: Majalah Ilmiah dan Informasi Kegeografian, 2021)
The Selo Gap area is geomorphologically located between mountains that have different types of characteristics. These differences have an impact on differences in the distribution pattern and characteristics of the springs. This research was conducted with the objectives of: 1) Analyzing the distribution pattern of springs in the Selo Gap landform unit, 2) Analyzing the characteristics of springs in the Selo Gap area. This study uses a survey-descriptive research method with a quantitative model. The sample of the springs in this study used a systematic sampling technique. The data collected is then analyzed descriptively which considers spatial aspects with nearest neighbor analysis. The results of this study indicate that: 1) The distribution pattern of the springs on the south side of Mount Merbabu based on the nearest neighbor analysis is known to have a z-score of 4.137440 which indicates a uniform or distributed type, 2) The characteristics of the springs in quantity have a high discharge category found in Tuk Babon with a discharge of 10 l/s and a low discharge found in Tuk Panguripan with a discharge of 0.008 l/s. The results of the multiparameter water quality analysis show that the relationship between parameters such as water temperature with DO, water temperature with DHL, and DHL with TDS runs uniformly and influences each other.